The Effect of Equity Perception on The Intention to Fraud in Medical Examination and Treatment with Health Insurance Cards in Vietnam - Thi Huong Mai; Thi Mai Mai (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
Health insurance is a hedge against financial risks, unexpected health losses, and expenditures (Folland, 2009). Therefore, health insurance helps to ensure social security. Health insurance is an important instrument to reduce the financial burden on people in general and beneficiaries in particular when providing medical care, thus making health services more accessible. In their efforts, the governments of all countries are aiming to make this type of insurance nationwide and comprehensive. However, along with the aim of increasing the coverage for the people related to medical examination and treatment costs, now a large part of the people is taking advantage and abusing the health insurance fund for personal interests. In the world, research on insurance fraud and abuse has been done in ethical or social aspects. However, the profiteering and abuse of health insurance funds in Vietnam is now attributed to many loopholes in the implementation process, thus leading to the idea that if others can do it, we can also do it. This study is conducted to examine the influence of perceived fairness in terms of the process, attitude, and distribution outcomes on the intention to fraud from health insurance. The sample of this study included 139 people who received medical examination and treatment with health insurance cards at hospitals in Hanoi city.